Емоційний стан здобувачів закладу вищої освіти та їхнє ставлення до вивчення іноземних мов (ІМ) у воєнний час - Барань Адальберт; Густі Ілона; Чотарі Юрій; Baran Adalbert; Huszti Ilona; Yurii Chotari; Bárány Béla; Csatáry György (Уманський державний педагогічний університет, 2024)
Резюме. У статті здійснено аналіз отримання уявлення про емоційний стан студентів, щоб глибше зрозуміти їхнє ставлення до вивчення ІМ під час війни. Розроблено онлайн-анкету, яку заповнили 194 студенти Закарпатського угорського інституту ім. Ференца Ракоці ІІ. Анкета містила блок запитань, що спрямовані на ставлення студентів до війни, а також на їхнє ставлення до вивчення іноземних мов під час війни. За допомогою анкетування здійснена спроба з’ясувати, як цей складний період вплинув на ставлення студентів до вивчення іноземних мов і які виклики їм довелося подолати. Результати показали, що здобувачі були оптимістичні, з надією дивилися на майбутнє Батьківщини. Здобувачі робили все можливе, щоб впоратися з навчальними обов’язками у цих складних умовах.

Abstract. The Russian invasion of Ukraine in February 2022 marked a turning point in the lives of countless Ukrainians. The sudden onset of war, coupled with the imposition of martial law, created a climate of uncertainty and fear. For students, this disruption meant adapting to new educational realities, including online learning and classes conducted in bomb shelters. The Ferenc Rákóczi II Transcarpathian Hungarian College, located in the westernmost region of Ukraine, was not immune to these challenges. Students faced daily air raid alerts, the stress of frequent relocation, and prolonged power outages. To better understand the impact of the war on students, this study sought to investigate their emotional state and attitudes towards language learning. An online questionnaire was administered to 194 students from various majors at the college. The survey included questions about their feelings regarding the war, their coping mechanisms, and their perspectives on English and German language learning during this period. The results of the study revealed a complex picture. While many students expressed initial worry about the outcome of the war, they also demonstrated a remarkable resilience and optimism for the future of their homeland. The study also identified several positive aspects. Many students found support from their teachers and classmates, who provided encouragement and understanding. One particularly encouraging finding was the positive impact of teacher feedback on student motivation. Many students reported that receiving constructive feedback from their teachers helped them stay engaged and motivated in their studies. This highlights the importance of supportive and encouraging relationships between students and their educators during times of crisis. In conclusion, the war in Ukraine has had a profound impact on the lives of students, both emotionally and academically. While the challenges they face are significant, many students have demonstrated remarkable resilience and adaptability. By understanding the emotional experiences of these students and providing appropriate support, it is possible to help them navigate these difficult times and emerge stronger.
Emotional state of higher education students and their attitude towards learning foreign languages in wartime
Редакційна колелія: http://znp.udpu.edu.ua/about/editorialTeam
Зміст: http://znp.udpu.edu.ua/issue/view/18604
Keywords: академічна успішність; вивчення мови; емоційний вплив; Закарпаття; зворотний зв’язок; мотивація; онлайн-навчання; онлайн-платформи; психічне здоров’я; стійкість; academic progress; language learning; emotional impact; Transcarpathia; feedback; motivation; online learning; online platforms; mental health; resilience